Carbon nanotubes as light absorbers in digital light processing three-dimensional printing of SiCN ceramics from preceramic polysilazane. Issue 11 (1st August 2020) - Xiao, Jun; Liu, Dongqing; Cheng, Haifeng; Jia, Yan; Zhou, Shen; Zu, Mei
Abstract: As a new method for producing dense ceramics with complex structures, digital light processing 3D printing technology has received considerable attention when applied to polymer-derived ceramics. In this study, using acrylate monomers, we developed a material system to modify the polysilazane preceramic polymers. Furthermore, during photopolymerization, the photocuring thickness was tuned using carbon nanotubes as light absorbers, thus improving the printing accuracy. The green body was printed and subsequently pyrolyzed to obtain the SiCN ceramic. We then managed to completely maintain the printed structure with uniform shrinkage being observed in all directions. The printed ceramic microstructures, denoting pyrolysis-induced microstructural changes, were characterized using scanning electron microscopy, X-ray diffraction, and transmission electron microscopy. This study paves the way for developing new approaches to obtain ultra-light and high-strength microwave-absorbing components that are suitable for aerospace applications by combining the SiCN ceramics of the unique dielectric properties with 3D printing technology to produce dense ceramics with periodic 3D structures.